Asuggestion of a training program to develop the skill of dribbling and shooting in basketball beginners-the case of young people from 9-12years old at the sports club biskra - شتيوي عبد المالك; خليل فاطمة الزهراء (sports creativity, 2025)
Study Summary the objective of this study was to determine the effectiveness of a proposed training program for skill development grabbling and shooting in basketball beginners, from 9- 12 years using the experimental approach in designing a single group while the sample consisted of 15 players for the sport club biskra city, we made the first measurement, then applied for 6 weeks divided into tow parts, the first part is the development of the skill of dribble and the secondpart of the development of skill shooting? and then we measured later. it has been processed the results which program spss, arithmetic average,normative dedeviation and t student thes results were in favor of subsequent measurement